Error Analysis of Japanese Toritatejoshi Nanka, Nante, Nado, and Kurai - J.D.L, Deajeng Dinda; Herniwati, Herniwati; Dewi J., Melia (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2020)
Hyouka no toritatejoshi or known as an evaluation of toritate particle is very important in Japanese language. But there are many toritate particles with similar function and meaning, which cause some difficulties for learners to differentiate. This study aimed to analyse the error of four Japanese toritate particles namely nanka, nante, nado, and kurai, evaluating the percentage of errors, type of errors, and identify the factors that caused error in using four toritate particles. The participants of this research were 45 Japanese language students. The instruments used in this study including interview, questionnaire, and a test. The results of this study showed that the error of toritatejoshi nado which shows quotation markers in sentences was the most common type of error. While the error of toritatejoshi kurai mostly when kurai particles combined with the other toritate particles (such as ~kurainara) was the least type of error. The factors that caused errors in using those toritatejoshi were mainly overgeneralization, followed by incomplete application of rules, false concept hypothesized, and the other special factors, respectively.